Soft Power and the Rise of the Global South: Chinese Investments in Renewable Energy in Brazil - Sampaio, Mateus de Almeida Prado [UNESP]; de Freitas, Elisa Pinheiro (Springer Nature, 2023)
This paper addresses the relationship between China and Brazil in the international energy scenario in the decade of 2010. In a context of preventing Global Warming and Climate Change, the relationship between these two countries seems to increase mainly in function of the investment flows that occur in the direction of East to West. Brazil is the country that generates more energy containing Chinese investments, and this generation is characterized mainly by the participation of renewable sources, especially hydroelectric, wind and solar. Through literature review, data tabulation and cartographic analysis, we present some of the recent directions of Chinese investments in energy production abroad. In the eastern hemisphere, Chinese investments are concentrated in the production of fossil energy from coal, carried out in neighboring countries. In the western hemisphere, they concentrate on renewable energy generation, notably hydraulics in South America and Africa. Brazil in place of primacy.